2019
DOI: 10.1021/acs.molpharmaceut.9b00970
|View full text |Cite
|
Sign up to set email alerts
|

Investigation into Intermolecular Interactions and Phase Behavior of Binary and Ternary Amorphous Solid Dispersions of Ketoconazole

Abstract: Conventionally, amorphous solid dispersions (ASDs) have been formulated as a binary matrix, but in recent years a new class of ASDs has emerged, where generally a second polymer is also added to the formulation. Having the presence of a second polymer necessitates a comprehensive solid-state characterization to study the intermolecular interactions and phase behavior on a molecular level. With this goal in mind, ketoconazole (KET) was selected as a model drug, and hydroxypropyl methyl cellulose (HPMC) and poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…For comparison, the carboxylic dimers between two indomethacin molecules could not be observed any more as the polymer concentration increased to 50% w/w. In a recent study, Sarpal et al used the SS-NMR technique to compare the molecular interactions in amorphous ketoconazole (KET), KET binary dispersions, and KET ternary dispersions [60]. A detailed 13 C SS-NMR deconvolution study showed that binary KET and poly (acrylic acid) (PAA) system exhibits higher prevalence of ionic and hydrogen bonds in comparison with its ternary system containing hydroxypropyl methyl cellulose (HPMC) [60].…”
Section: Solid-state Nuclear Magnetic Resonance (Nmr)mentioning
confidence: 99%
See 1 more Smart Citation
“…For comparison, the carboxylic dimers between two indomethacin molecules could not be observed any more as the polymer concentration increased to 50% w/w. In a recent study, Sarpal et al used the SS-NMR technique to compare the molecular interactions in amorphous ketoconazole (KET), KET binary dispersions, and KET ternary dispersions [60]. A detailed 13 C SS-NMR deconvolution study showed that binary KET and poly (acrylic acid) (PAA) system exhibits higher prevalence of ionic and hydrogen bonds in comparison with its ternary system containing hydroxypropyl methyl cellulose (HPMC) [60].…”
Section: Solid-state Nuclear Magnetic Resonance (Nmr)mentioning
confidence: 99%
“…In a recent study, Sarpal et al used the SS-NMR technique to compare the molecular interactions in amorphous ketoconazole (KET), KET binary dispersions, and KET ternary dispersions [60]. A detailed 13 C SS-NMR deconvolution study showed that binary KET and poly (acrylic acid) (PAA) system exhibits higher prevalence of ionic and hydrogen bonds in comparison with its ternary system containing hydroxypropyl methyl cellulose (HPMC) [60]. In recent studies, two-dimensional (2D) ss-NMR was also developed to identify the type and strength of various drug-polymer interactions in ASDs with enhanced sensitivity and resolution [61,62].…”
Section: Solid-state Nuclear Magnetic Resonance (Nmr)mentioning
confidence: 99%
“…Interestingly, 3FN shows a similar 1 H T 1 of the two components but distinct 1 H T 1rho values, suggesting a partially homogeneous system. It is worth mentioning that 2FN and 3FN have identical one-dimensional 13 C spectra (data not shown), suggesting that the two ASDs do not have distinctly different molecular structures and interactions, regardless of the level of mixing [ 28 , 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, ssNMR has been utilized to assess the homogeneity of drug substances and polymer in ASDs at a high-resolution and to successfully correlate such microscopic attributes to the formulation processes [23,[26][27][28][29]. 1 H T 1 and T 1rho values of individual components were measured as described in the method section and were compared to evaluate the homogeneity.…”
Section: Homogeneity Of Drug and Polymer Determined As By Solid-state Nmr (Ssnmr)mentioning
confidence: 99%
“…The capability of NMR to characterize this complex ternary ASD has been demonstrated using KTZ-HPMC-PAA ASD. 52 While no changes in chemical shift were highlighted in the 13 C spectra for the binary system KTZ-HPMC ASDs (Figure 3a) and the possibility of an interaction between the compounds was excluded, 13 C spectroscopic data for both KTZ-PAA and KTZ-HPMC-PAA dispersions (Figure 3b,c) showed some interesting similar spectral features. In both systems, the intensity of the peak corresponding to the PAA dimer form (at 182 ppm) decreases with respect to the free form (at 177 ppm); the intensity across the drug loading changes and, interestingly, a new peak at 172 ppm emerges, which corresponds to hydrogen bonded KTZ.…”
Section: Chemical Shift As a Unique Observable Of The Api−polymer Int...mentioning
confidence: 91%